The rise of global policy networks in education: analyzing Twitter debates on inclusive education using social network analysis - Schuster, J.; Jörgens, H.; Kolleck, N. (Journal of Education Policy, 2021)
With the Convention on the Rights of Persons with Disabilities (CRPD), inclusive education has become the main alternative to special schools for the schooling of children with disabilities. In order to promote the global implementation of inclusive education, a variety of stakeholders form networks to transmit and exchange information and knowledge concerning political strategies. However, little is known about the actors and actor groups involved in these networks. In the present paper, we draw on general network theory and policy network theory to examine the Twitter communication network that has formed around the topic of inclusive education. Using exploratory and inferential social network analysis, we show that disabled persons’ organizations and international organizations, such as the United Nations, hold a particularly central position in the network. This position enables them to potentially exert influence on the content and flow of information within the network. Aside from that, business actors are active participants in the network. Moreover, the Twitter network shows some structural patterns that can also be found in policy networks. Our findings help to map the global sphere of inclusive education promotion and can contribute to a broader understanding of global processes in inclusive education policy.